The analysis of association between alleles of VDR, Col1a1 and CALCR genes with physical performance in rowers - Moskalenko, M.; Glotov, O.; Glotov, A.; Rogozkin, V.; Ivanchenko, T.; Baranov, V. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
It is well known that formation, manifestation and development of physical features of human are subjected to complicated interaction of his genetic component and environment. It shows the influence of individual genetic predisposition to manifestation of physical features of human, which develops according to biosocial conditions. The investigations of human predisposition to carrying-out physical works extend positions in genetics of sports. The identification of the genetic polymorphism allow to predict the development of physical features of human and has the great practical sense for effective choosing of the athletes carrying heavy physical works. The products of genes of bone tissue metabolism take part in forming of definite physical status of the organism. The most intensive studies deal with the definition of the rate of association between vitamin D receptor gene (VDR) variants and bone mineral density, and also between alleles of calcitonin receptor gene (CALCR), collagen type 1 gene polymorphism (Col1a1) with mass and strength of bone. Methods The allele rates of VDR, Col1a1 and CALCR genes in 59 non-related men from Northwest Russian population and in 57 rowers from Saint Petersburg were investigated. The polymorphisms of VDR, Col1a1 and CALCR genes were tudied by PCR-RFLP method. Results The frequency of allele t (Taq I polymorphism in exon 9 of VDR gene) in the group of rowers was 40.4%. It was significantly higher (p<0,01) than in population group (28.7%). The frequency of tt genotype was higher in the group of rowers (19.3%) compared with the population group (9.3%) (Fig. 1). Analysis of the Apa I polymorphism in Sp1 transcription factor binding site of regulating site in Col1a1 gene did not reveal significant differences (p>0,05) of the genotype`s frequencies in studied groups (rowers - SS-77.2%, Ss-19.3%, ss-3.5%; population - SS-77.2%, Ss-22.8%, ss-0.0%). The frequency of allele s in the group of rowers was 13.2% and did not differ significantly (p>0,05) from the average in the population group (11.4%). Alu I polymorphism (C/T change in 463 codone) of CALCR gene was investigated also. We have found significant differences (p<0,01) of the frequencies of genotypes for this polymorphism in two studied groups (rowers - TT-70.2%, TC-17.5%, CC-12.3%; population- TT-54.2%, TC-33.9%, CC-11.9%) (Fig. 1). The frequency of allele T in the group of rowers was 78.9% and did not differ significantly (p>0,05) from the average in population (71.2%). Discussion/Conclusion The results suggest that the athletes have tt (VDR), TT (CALCR) genotypes may be more successful in sport. Accordingly our findings perspectives and predictable expediency of using genetic predisposition analysis as one of the basic method in formation of Olympic and other teams are under discussion.